McGraw-Hill's essential ESL grammar : a handbook for intermediate and advanced ESL students - Lester, Mark, author (New York : McGraw-Hill, 2008)
This book covers more than the basics of English. The author has developed an innovative method to help you conquer tricky subjects such as articles, tense, verb complements, word order, and more
pt. 1. Noun phrases -- Nouns -- Adjectives -- Determiners -- Post-noun modifiers -- Pronouns -- Gerunds and infinitives -- Noun clauses -- pt. 2. Verb phrases -- Basic verb forms -- Verb tenses and modals -- Special verbs -- Verb complements I : simple complements -- Verb complements II : multiple complements -- Predicate adjective complements -- Adverbs -- Using adverbs -- pt. 3. Sentences -- Conjunctions -- Questions -- The passive
Includes index
English text.
Keywords: English language -- Textbooks for foreign speakers; English language -- Grammar -- Problems, exercises, etc; English language -- Textbooks for second language learners